2013
DOI: 10.1097/scs.0b013e31828b7456
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Studies of Different Flaps for Reconstruction of Buccal Defects

Abstract: Our purpose was to evaluate the feasibility of radial forearm free (RFF) flap, platysma myocutaneous (PM) flap, and anterolateral thigh (ALT) flap in buccal reconstruction. This study consisted of 56 patients who were categorized into 3 groups. The Student t test was used to analyze the variables. Patients in group platysma flap were significantly older, the dissection of platysma flap was easier, and the defect was significantly smaller than those in group radial forearm flap and group ALT flap. The reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…The procedure is useful for repairing head and neck defects, as it provides reliable anatomy, long pedicle length, good size vessels, sufficient skin thickness and lack of hair. 2,3 Donor site complications can arise, however, including poor cosmetic appearance and functional morbidity following the sacrifice of a major artery.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure is useful for repairing head and neck defects, as it provides reliable anatomy, long pedicle length, good size vessels, sufficient skin thickness and lack of hair. 2,3 Donor site complications can arise, however, including poor cosmetic appearance and functional morbidity following the sacrifice of a major artery.…”
Section: Introductionmentioning
confidence: 99%
“…2 Distal partial necrosis occurred in 1 flap, but all flaps survived. 2 Distal partial necrosis occurred in 1 flap, but all flaps survived.…”
Section: Resultsmentioning
confidence: 98%
“…2 In order to identify Candida dubliniensis from C. albicans, isolates were selected to incubate on Sabouraud agar at 37°C and 42°C. A Gramstained smear was assessed by microscopy for the presence of yeasts.…”
Section: Clinical Reportmentioning
confidence: 99%
“…Originally, it was thought that, by altering the mandibular position, anteriorly displaced disks could be "recaptured," after which the new condyledisk relationship could be "stabilized" through comprehensive dental or surgical occlusal procedures. 2 Understanding mechanisms of action for functional appliances is critical for treating and retaining the achieved corrections in DDWR patients associated with class II mandibular retrognathism. Although different studies have reported the efficiency of functional appliance, the biomechanics by which the temporomandibular joint (TMJ) remodeling is still a matter of controversy.…”
Section: Discussionmentioning
confidence: 99%
“…It has some well-known advantages: a reliable anatomy, long pedicle length, good size vessels, suitable thinness, and relative sparsity of hair to substitute head and neck defects. 2 Although the primary intended outcome of head and neck malignancies surgery is still the disease-free survival of the patient, quality of life (QoL) is now seen as an essential secondary outcome. 3 The QoL is a global construct that has developed during the past 3 decades in response to the perceived need to assess the patient's overall sense of wellbeing and how it relates to disease and disease treatment.…”
mentioning
confidence: 99%